2007
DOI: 10.1375/twin.10.4.649
|View full text |Cite
|
Sign up to set email alerts
|

Does a Probability of Breech Presentation of More Than 50% Exist Among Diseases and Medical Conditions?

Abstract: The aim was to study the effect of twin gestations in a uterus with 2 bodies on the probability of breech presentation at delivery. The hypothesis was that the probability of breech presentation was not higher than 50%. A review was undertaken of MEDLINE (1966–2004) and of the article reference list for statistical analysis of presentation at delivery among twins in a normal uterus, singleton gestations in a uterus with 2 bodies, and case studies of twins in a uterus with 2 bodies. There are 10 studies of twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…These data are related to either single series or collections of series dealing with the incidence of breech presentation in medical conditions and diseases, data obtained from repeated observations under the same conditions, as well as series of two concomitant medical conditions. Studies of more than 50 known diseases and medical conditions with the incidence of breech presentation higher than that occurs in the general population revealed that the probability of breech presentation is around 50% or less (Table I) [10,11,12]. This is also related to studies of intergeneration recurrence [13], and the probability of breech presentation after previous breech deliveries [14].…”
Section: Probability Of Breech Presentationmentioning
confidence: 88%
“…These data are related to either single series or collections of series dealing with the incidence of breech presentation in medical conditions and diseases, data obtained from repeated observations under the same conditions, as well as series of two concomitant medical conditions. Studies of more than 50 known diseases and medical conditions with the incidence of breech presentation higher than that occurs in the general population revealed that the probability of breech presentation is around 50% or less (Table I) [10,11,12]. This is also related to studies of intergeneration recurrence [13], and the probability of breech presentation after previous breech deliveries [14].…”
Section: Probability Of Breech Presentationmentioning
confidence: 88%
“…If the fetus in this period does not have enough space, it will not turn from breech to cephalic presentation. Since before this period the probabilities of breech and cephalic presentations are equal, the frequency of breech presentation in case of the cornual-fundal location of the placenta should not exceed 50% (12,13). The distribution of breech presentation in different studies, including this study, was from 27.3% to 39.86%, which supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Breech presentation incidence is influenced by both fetal and maternal diseases along with other medical conditions. Occurrence of these factors, higher the probability of breech presentation between 4% to 50% [2,3]. Failure of the fetus to turn to a cephalic presentation will lead to breech presentation at delivery.…”
Section: Introductionmentioning
confidence: 99%